Do you know this syndrome? - Guida Santos; Sara Lestre; Alexandre João (Sociedade Brasileira de Dermatologia, 2013)
POEMS syndrome is a unique clinical entity, the diagnosis of which is made when polyneuropathy and monoclonal gammopathy occur together, associated with other changes such as organomegaly, endocrinopathy, skin changes and papilledema. Cutaneous manifestations are heterogeneous, with diffuse cutaneous hyperpigmentation, hemangiomas and hypertrichosis occurring more frequently. We report the case of a 65- year-old female patient with this syndrome, diagnosed after 15 years of disabling peripheral neuropathy.